An Integrated Governance-Risk Framework: Examining the Influence of Corporate Governance and Credit Risk Management on the Financial Performance and Sustainability of Rural Banks in the Philippines - Christine Aguirre Cayanan (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2026)
The sustainability and resilience of rural banks have become increasingly important amid rapid digital transformation, evolving regulatory requirements, and heightened risk exposures. This study examined the combined influence of corporate governance and credit risk management practices on the financial performance of rural banks in the Philippines using an Integrated Governance-Risk Framework. A quantitative descriptive-correlational research design was employed involving 54 respondents from 18 rural banks in Central Luzon. Primary data were collected through structured questionnaires, while secondary data were obtained from the Bangko Sentral ng Pilipinas (BSP) Data Center and published financial statements . Descriptive statistics, Pearson correlation, and multiple regression analyses were used to examine the relationships among the variables. The findings revealed that rural banks exhibited high levels of corporate governance and credit risk management implementation. Corporate governance practices significantly influenced financial performance, demonstrating that stronger governance contributes to improved profitability and organizational effectiveness. In contrast, credit risk management practices showed no significant direct effect on financial performance, although they remained essential in maintaining financial stability, asset quality, and regulatory compliance. The study concludes that integrating sound corporate governance with effective credit risk management provides a comprehensive framework for enhancing the financial performance, sustainability, and long-term resilience of rural banks in the Philippines